PENDIDIKAN KESEHATAN PADA CALON PENGANTIN (CATIN) USIA MUDA MENDUKUNG PENGAMBILAN KEPUTUSAN ALAT KONTRASEPSI - Eva Liviana Prince Arisandi; Purnamasari, Desy; Renita Rizkya Danti (WOMB Midwifery Journal, 2023)
Early marriage is a marriage carried out by a couple under the age of 17 years. The prevalence of child marriage in 2019 in Indonesia was 10.35%. In East Java province it reached 3.6% and Situbondo Regency 2.4% in 2019. Meanwhile, data on child marriage at the Klampokan Community Health Center in 2019 was 1.5%. Health education regarding contraceptives for prospective brides and grooms is still lacking. This study aims to determine the effect of health education for prospective brides (catin) under 20 years of age on contraceptive decision making at the Klampokan Situbondo Community Health Center. This research is experimental research with a static group comparison design. The total sample was 44 respondents using total sampling which was divided into 2 groups of 22 people each. The intervention group was given health education using a decision-making aid sheet (ABPK) and the control group independently received information about family planning. The instruments used were flip sheets and observation sheets. Data analysis used the Wilcoxon test with SPSS. The research results showed that 31 respondents (70.5%) made the decision to get pregnant using contraception and 13 respondents (29.5%) made the decision not to get pregnant. There is an influence of health education for prospective brides and grooms (CATIN) under 20 years of age on contraceptive decision making at the Klampokan Situbondo Community Health Center (p 0.000 < 0.05). It is hoped that women who are under 20 years of age will end the pregnancy because at that age the reproductive organs are still not mature and ready.